# In each of the fo

We have,

f(x) = 2x4-6x3+2x2-x+2 and g(x) = x+2

Therefore, by remainder theorem when f (x) is divided by g (x) = x – (-2), the remainder is equal to f (-2)

Now, f(x) = 2x4-6x3+2x2-x+2

f (-2) = 2 (-2)4 – 6 (-2)3 + 2 (-2)2 – (-2) + 2

= 2 * 16 + 48 + 8 + 2 + 2

= 32 + 48 + 12

= 92

Hence, required remainder is 92.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Master the Art of Writing Chemical Formulae42 mins  Combinations of Solids43 mins  Law of Gravitation40 mins  Master Mole Concept in 45 Minutes48 mins  Quick Recap of Cell62 mins  Newton's Second Law46 mins  Final Phase & Legacy of the Revolution43 mins  Variation in g with Rotation of Earth42 mins  Circles- All kinds of Questions36 mins  Arc of Circle And Related IMP Qs40 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x31</sRS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x3RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics